Chaplains to the Imprisoned : Sharing Life with the Incarcerated. - Pallone, Letitia C. (Taylor and Francis, 2014)
Chaplains to the Imprisoned begins to fill the information gap through its in-depth study of prison chaplains as seen by co-workers, inmates, and the chaplains themselves. They describe their roles, share difficulties which are encountered in their ministry, and personal methods for coping with these difficulties, especially those which may be internalized as stress. The author, a Roman Catholic priest with a doctorate in criminal justice, provides a fascinating look into the work of chaplains who serve in correctional institutions. This new book sheds a much-needed light on the ofte.